2004
DOI: 10.1248/cpb.52.498
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide as a Nitric Oxide Synthase Inhibitor and Its Structural Development

Abstract: Thalidomide has been found to exhibit weak nitric oxide synthase (NOS)-inhibitory activity. Structural development studies of thalidomide showed that some N-2,6-dimethylphenylhomophthalimide analogs possess NOS-inhibiting activity.Key words thalidomide; nitric oxide synthase (NOS); inhibitor; structural development Thalidomide (1) is a hypnotic/sedative drug that was withdrawn from the market because of its severe teratogenicity. [2][3][4] In spite of this, research into thalidomide was not halted, and the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…These results may be supported by the previous studies demonstrating that NOSinhibitory activity of thalidomide in vitro is weak. 26) Second, we examined the effects of thalidomide on the constitutive expression and endotoxin-induced down-regulation of CYP3A2 using Western blot analysis. This experiment revealed that thalidomide had no effect on the constitutive expression of CYP3A2, and the degree of the decreased protein levels of CYP3A2 was greater in endotoxin plus thalidomide-treated rats than that in endotoxin-treated rats, which can be agreed well with the results obtained from the antipyrine clearance experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be supported by the previous studies demonstrating that NOSinhibitory activity of thalidomide in vitro is weak. 26) Second, we examined the effects of thalidomide on the constitutive expression and endotoxin-induced down-regulation of CYP3A2 using Western blot analysis. This experiment revealed that thalidomide had no effect on the constitutive expression of CYP3A2, and the degree of the decreased protein levels of CYP3A2 was greater in endotoxin plus thalidomide-treated rats than that in endotoxin-treated rats, which can be agreed well with the results obtained from the antipyrine clearance experiment.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] There are interesting reports suggesting that thalidomide improves endotoxin-or alcohol-induced liver injury, 22,23) and prolongs the survival rate following the experimental sepsis induced by endotoxin or bacterial challenge in rats. 24,25) Shimazawa et al 26) have reported that thalidomide and its analogs have NO synthase (NOS)-inhibitory activity in vitro, but the activity of thalidomide is weak. Enomoto et al 27) reported that thalidomide abolishes the endotoxin-induced increase in CD14 expression in Kupffer cells in vitro.…”
mentioning
confidence: 99%
“…Figure 8. LXR antagonistic activities of PP2P (7), PP50 (23), and 5CPPSS-50 (8) measured by means of reporter gene assay. Various concentration of the test compounds were added in the presence of 0.1 lM T0901317.…”
Section: Mode Of Tubulin Polymerization-inhibition By 5hpp-33mentioning
confidence: 99%
“…These findings suggested that thalidomide 1 is a multi-target drug, and this, in turn, implied the possible usefulness of thalidomide 1 as a template for development of various kinds of medicaments. In fact, various biologically active compounds, such as TNF-a production regulators (including bi-directional ones, pure inhibitors, and pure enhancers) [7,8], androgen antagonists [9 -11], aminopeptidase inhibitors [12 -15], a-glucosidase inhibitors [16 -18], thymidine phosphorylase inhibitors [19], cyclooxygenase (COX) inhibitors [20 -22], nitric oxide synthase (NOS) inhibitors [23,24], histone deacetylase (HDAC) inhibitors [25 -27], anti-angiogenic agents [28,29], tubulin polymerization inhibitors [30 -32], cell differentiation inducers [33], and liver X receptor (LXR) antagonists [34,35] have been developed based on the structure of thalidomide 1 ( Fig. 2 and 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation